ANALYSIS OF RAINFALL PATTERNS IN THE NUSA TENGGARA REGION USING THE FAST FOURIER TRANSFORM (FFT) METHOD AND ITS RELATIONSHIP WITH EL-NIÑO AND IOD - Agustina, Atika; Akhsan, Hamdi; Ariska, Melly; Suhadi, Suhadi; Andriani, Nely (Universitas Mataram, 2025)
Changes in rainfall patterns have a significant impact on agriculture and water management in arid regions such as Nusa Tenggara. Water availability in this region is highly dependent on rainfall, which is influenced by global climate phenomena such as El-Niño and the Indian Ocean Dipole (IOD). This study aims to analyze the characteristics of rainfall patterns and analyze the relationship between rainfall and the El-Niño and IOD phenomena. Daily rainfall data from three BMKG observation stations in West Nusa Tenggara and East Nusa Tenggara during the period 1983-2022 were used in the analysis. The Fast Fourier Transform (FFT) method is used to identify periodic cycles, while the Pearson correlation test is used to determine the relationship of rainfall with El-Niño and IOD. The analysis shows that the Nusa Tenggara region is characterized by a monsoonal rainfall pattern with an annual cycle (12 months). Peak rainfall occurs in January and December, while the dry season lasts from July to September. The correlation of rainfall with El-Niño shows a weak negative relationship, while the influence of IOD is very small and varies between locations. The analysis shows that the rainfall pattern in the Nusa Tenggara region is monsoonal with an annual cycle (12 months) and semi-annual cycle (6 months). The peak of rainfall occurs from December to January, while the dry season lasts from July to September. The relationship between rainfall and El-Niño shows a weak negative correlation, so that when El-Niño increases, rainfall tends to decrease, and vice versa. The influence of IOD on rainfall is very small and varies between locations. Overall, while both El-Niño and IOD affect rainfall, their impact in the region is weak and more significant when both phenomena occur together.